Peningkatan Hasil Belajar Pendidikan Pancasila dengan Model Inquiry Berbantuan Media Audio Visual di Kelas IV SD Negeri 16 Padang Besi Kota Padang - Monalisa Septrianingsih; Ari Suriani; Yesi Anita; Mansurdin Mansurdin (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research is motivated by the low learning outcomes of students caused by the lack of learning activities involving students, as the learning process is still centered on the teacher. This makes students less active in participating in learning. This study aims to describe the improvement in student learning outcomes in Pancasila and Citizenship Education learning using the Inquiry model assisted by audio-visual media in class IV of SDN 16 Padang Besi, Padang City. The type of research used is classroom action research (CAR) with qualitative and quantitative approaches, carried out in two cycles. The research procedure consists of planning, implementation, observation, and reflection. The data obtained are related to learning outcomes using the Inquiry model assisted by audio-visual media. Data collection techniques include observation, tests, and non-tests. The research subjects involved class teachers as observers, researchers as practitioners, and 26 class IV students. The results of the study show that: first, the cycle I teaching module obtained an average of 85.3% (B), increasing in cycle II to 95% (SB). Second, the implementation results of the teacher's learning aspects in cycle I reached 82% (B), increasing in cycle II to 96% (SB). Third, the implementation results of the students' learning aspects in cycle I were 82% (B), increasing to 96% (SB) in cycle II. Fourth, the average student learning outcomes in cycle I were 77 (C), increasing to 89 (B) in cycle II. Thus, it can be concluded that the Inquiry model can improve student learning outcomes in Pancasila and Citizenship Education learning.